2013
DOI: 10.1111/bph.12445
|View full text |Cite
|
Sign up to set email alerts
|

The Concise Guide to PHARMACOLOGY 2013/14: G Protein‐Coupled Receptors

Abstract: The Concise Guide to PHARMACOLOGY 2013/14 provides concise overviews of the key properties of over 2000 human drug targets with their pharmacology, plus links to an open access knowledgebase of drug targets and their ligands (www.guidetopharmacology.org), which provides more detailed views of target and ligand properties. The full contents can be found at http://onlinelibrary.wiley.com/doi/10.1111/bph.12444/full.G protein-coupled receptors are one of the seven major pharmacological targets into which the Guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
336
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(352 citation statements)
references
References 1,600 publications
(861 reference statements)
1
336
0
3
Order By: Relevance
“…Previous experiments, as those reported in [22] and [27], have shown that the maximum lag is to be found in the range [1,160]. Following [27], and the rationale that a large maximum lag implies high data dimensionality and the problems that come with it (curse of dimensionality), we searched for L in the range of 1 to 30.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments, as those reported in [22] and [27], have shown that the maximum lag is to be found in the range [1,160]. Following [27], and the rationale that a large maximum lag implies high data dimensionality and the problems that come with it (curse of dimensionality), we searched for L in the range of 1 to 30.…”
Section: Resultsmentioning
confidence: 99%
“…In this section, we simulate a process of deorphanization of some sequences which are known to belong to the class C GPCR family [30,1] but for whom the corresponding natural ligand is unknown. For this, we developed a novel inductive version of the naturally transductive SS-GTM model.…”
Section: Deorphanization Experiments Using An Inductive Version Of Ss-gtmmentioning
confidence: 99%
“…This nomenclature complies with the British Journal of Pharmacology's guidelines (Alexander et al, 2013). In the past decade, GPBA has been shown to mediate many of the nongenomic actions of BAs on thermogenesis, insulin secretion and glucose homeostasis, inflammation, digestive functions and sensory transduction.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of other G-protein cannabinoid receptors has also been suggested. These proposed receptors (also called putative or nonclassical cannabinoid receptors) include GPR18, GPR55 and GPR119 that have structural similarity to CB 1 and CB 2 (Alexander et al 2013;Zubrzycki et al 2014). …”
Section: The Endocannabinoid System and Classification Of Cannabinoidsmentioning
confidence: 99%